A primary study on the brewing technique of orange wine - WANG You-yong; HE Guo-qing (浙江大学学报. 农业与生命科学版, 2000)
A new technique was studied by using fresh orange without seeds to produce a dry wine. The effects of extraction, yeast and main fermentation temperature on the quality of the wine was discussed. The result showed that a new type of orange wine with unique flavour and taste would be produced using oranges under following conditions of which orange juice was manually extracted, inoculated by yeast No. 1, incubated at 23 ℃, then followed by filtration, clarification and maturation.